Effectiveness of Virtual Team for Improving Communication Breakdown in IBS Project Delivery Process - Ahmad Pozin, Mohd Affendi; Mohd Nawi, Mohd Nasrun; Romle, Abdul Rahim (International Journal of Supply Chain Management, 2016)
Technological innovation and globalization force the organizations collaborate across time, culture, and geographical boundaries. It becomes one of the ordinary practices to the construction sector and has given rise to the concept of global teams known as a virtual team. Virtual team drives by advance technology to solve the communication issues and perceived as an effective, efficient, and creative team structure. Effective communication is an essential process to develop project success in the construction Industrialised Building System (IBS) project. However the implication of the fragmented approach in the IBS project development process was reflected in the lack of communication between multidisciplinary project teams cause various problem such as lower performance and a higher turnover of staff. Therefore, this research aims to investigate the effects of communication, subject to different project stage and to identify the key factors to enhance virtual team communication processes between the practitioners.